Pengaruh Beban Kerja, Lingkungan Kerja, dan Disiplin Kerja terhadap Loyalitas Karyawan melalui Kepuasan Kerja di PT. Sentratek Adiprestasi Surabaya - Septiyan Intan Purnama; Wulan Purnamasari (Nirta Learning Centre, 2025)
This study is intended to prove and analyze the influence of workload, work environment, and work discipline on employee loyalty through mediation variable work satisfaction at PT. Sentratek Adiprestasi Surabaya. Using a descriptive quantitative research method with a non-probability sampling technique using a saturated sampling technique with a sample size of 55 respondents. Data processing using SMARTPLS 4 software, the tests carried out were Validity Test, Reliability Test, Outer Model Test (Convergent Validity, Discriminant Validity, Composite Reliabity), InneModel Test (R-Square, F-Square, Path Analysis), and Hypothesis Test. The results of this study indicate 1) Workload has a positive and significant effect on Job Satisfaction with a P-Value of 0.000 <0.5. 2) Work Environment has a positive and significant effect on Job Satisfaction with a P-Value of 0.001 <0.5. 3) Work Discipline has a positive and significant effect on Job Satisfaction with a P-Value of 0.001 <0.5. 4) Workload has a positive and significant effect on Employee Loyalty with a PValue of 0.033 <0.5. 5) Work Environment has a positive and significant effect on Employee Loyalty with a P-Value of 0.012 <0.5. 6) Work Discipline has a positive and significant effect on Employee Loyalty with a P-Value of 0.002 <0.5. 7) Job Satisfaction has a positive and significant effect on Employee Loyalty with a P-Value of 0.000 <0.5.